Audit on antenatal care of obese pregnant patients as per protocol - Khan, Farheen; Bagtharia, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Obesity in pregnancy is associated with increased risks for both the mother and the fetus, including complications such as gestational diabetes mellitus (GDM), hypertensive disorders, and venous thromboembolism (VTE). The Royal College of Obstetricians and Gynaecologists (RCOG) has issued the Green-top Guideline No. 72: 2018 on "Care of Women with Obesity in Pregnancy" to provide evidence-based recommendations. Audit was undertaken at the Basildon and Thurrock University Hospital, between July to August 2024 to evaluate the antenatal care of obese pregnant patients as per the guideline. Retrospective data collected of 40 patients from Medway and antenatal notes of the patients. Study revealed that, for 100% patients VTE score was assessed and they were prescribed anticoagulant, if needed. Need for aspirin was assessed in 100% patients, and patients were prescribed aspirin as per the score.100% patients were screened for GDM between 24-28 weeks, howsoever, only 50% patients were reweighed in third trimester. Audit revealed strengths in majority of areas, such as VTE assessment, GDM screening at 24-28 weeks, prescribing inhixa and assessing need for aspirin. However, gaps were noted in the reweighing process in the third trimester.